Association of Serum Lipids with High Blood Pressure among Diabetic Patients - Hossain, Md. Sharif; Talukder, Rajee Mahmud; Haque, Md. Enamul; Masum, Md.; Sultana, Fathima; Milon, Md. Sarowar Uddin (Archives of Clinical and Biomedical Research, 2023)
Background: The intricate interplay between serum lipid levels and high blood pressure in diabetic patients has emerged as a critical nexus in contemporary medical research. As diabetes poses a multifaceted challenge to cardiovascular health, understanding the nuanced relationship between serum lipids and hypertension becomes imperative. This study delves into the intricate dynamics, exploring how variations in lipid profiles may influence blood pressure regulation in diabetic individuals. Unraveling these associations holds the key to developing targeted interventions that mitigate the heightened cardiovascular risks faced by diabetic patients, paving the way for more effective management and improved overall health outcomes. Aim of the study: This study aimed to evaluate the association of serum lipids with high blood pressure among diabetic patients. Methods: This observational study occurred at the Department of Medicine in National Institute of Cardiovascular Disease (NICVD), Dhaka, Bangladesh. The study included a cohort of 123 individuals diagnosed with diabetes. The research spanned one year, commencing from January 2021 to December 2021.The research included comprehensive assessments, blood pressure checks, and blood sample collection. Inclusion criteria covered type-1 and type-2 diabetic patients, while exclusion criteria excluded children, pregnant diabetic women, those with end-stage renal disease, on dialysis, or with active hepatic disease. Hypertension was defined as blood pressure ≥140/90. Fasting blood samples measured cholesterol levels. Data analysis utilized IBM SPSS Statistics, and statistical significance was set at p<0.05. The study aimed for 90% statistical power, presenting data as percentages with mean±SD and 95% confidence intervals. Results: This study analyzes a diabetic patient cohort's demographic and health characteristics. Of 123 participants, 56.09% were male, 82.93% had Type-2 diabetes, and 68.18% lacked hypertension. Lipid analysis revealed abnormal levels in 64.55%. Descriptive statistics include a mean age of 49.84 years and a diabetes duration of 13.37±4.58 years. Correlation analysis shows positive links between blood pressure and various lipids. Regression models indicate significant associations between systolic/ diastolic blood pressure and triglycerides, cholesterol, LDL-C, HDL-C, and Non-HDL-C. These findings emphasize the intricate relationship between blood pressure and lipid levels in diabetic patients. Conclusion: This study reveals a significant association between serum lipid levels and high blood pressure in diabetic patients. Elevated lipids may serve as a predictive factor for hypertension in this population. Understanding these links is crucial for targeted interventions to mitigate cardiovascular risks and improve overall health outcomes in diabetic individuals.